2022
DOI: 10.1111/1462-2920.15960
|View full text |Cite
|
Sign up to set email alerts
|

CotG controls spore surface formation in response to the temperature of growth in Bacillus subtilis

Abstract: Bacterial spores of the Bacillus genus are ubiquitous in nature and are commonly isolated from a variety of diverse environments. Such wide distribution mainly reflects the spore resistance properties but some Bacillus species can grow/sporulate in at least some of the environments where they have been originally isolated. Growing and sporulating at different conditions is known to affect the structure and the resistance properties of the produced spore. In B. subtilis the temperature of growth and sporulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…To verify whether GHyb was functional, Western blotting experiments were performed on proteins extracted from purified spores of a wild-type strain and strains expressing GHyb with and without the kinase CotH. Anti-CotG antibody, raised against the N-terminal 14 residues of B. subtilis CotG ( 18 ), and anti-protein kinase C (anti-PKC) antibody, recognizing phosphorylated serine residues ( 18 ), were reacted against the extracted proteins. As previously reported, CotG was extracted from wild-type spores in two forms (CotG 36 and CotG 32 ), and both proteins were not found in extracts of spores of a strain lacking CotH ( 12 , 20 ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To verify whether GHyb was functional, Western blotting experiments were performed on proteins extracted from purified spores of a wild-type strain and strains expressing GHyb with and without the kinase CotH. Anti-CotG antibody, raised against the N-terminal 14 residues of B. subtilis CotG ( 18 ), and anti-protein kinase C (anti-PKC) antibody, recognizing phosphorylated serine residues ( 18 ), were reacted against the extracted proteins. As previously reported, CotG was extracted from wild-type spores in two forms (CotG 36 and CotG 32 ), and both proteins were not found in extracts of spores of a strain lacking CotH ( 12 , 20 ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CotC and CotU, two highly homologous small coat proteins that assemble on the spore coat in multiple forms ( 22 , 23 ), fail to assemble in a strain lacking CotH ( 17 ). Such an effect, due to the accumulation of unphosphorylated CotG in the mother cell cytoplasm ( 18 ), is not observed when the central repeats of CotG (G Δcentral ) were deleted ( 15 ). Western blotting experiments showed that all forms of CotC and CotU were present in coat extracts of strains carrying GHyb as the only CotG form, independently from the presence of CotH ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations